Camera-based detection of properties of biogenic solid fuels to determine fuel quality categories - Lukas, Johannes; Kolb, Sebastian; Plankenbühler, Thomas; Karl, Jürgen (6th Doctoral Colloquium Bioenergy, 2023)

Capillary Interactions, Aggregate Formation, and the Rheology of Particle-Laden Flows: A Lattice Boltzmann Study - Yang, Lei; Sega, Marcello; Leimbach, Steffen; Kolb, Sebastian; Karl, Jürgen; Harting, Jens (Industrial & Engineering Chemistry Research, 2022)
The agglomeration of particles caused by the formation of capillary bridges has a decisive impact on the transport properties of a variety of at a first sight very different systems such as capillary suspensions, fluidized beds in chemical reactors, or even sand castles. Here, we study the connection between the microstructure of the agglomerates and the rheology of fluidized suspensions using a coupled lattice Boltzmann and discrete element method approach. We address the influence of the shear rate, the secondary fluid surface tension, and the suspending liquid viscosity. The presence of capillary interactions promotes the formation of either filaments or globular clusters, leading to an increased suspension viscosity. Unexpectedly, filaments have the opposite effect on the viscosity as compared to globular clusters, decreasing the suspension viscosity at larger capillary interaction strengths. In addition, we show that the suspending fluid viscosity also has a nontrivial influence on the effective viscosity of the suspension, a fact usually not taken into account by empirical models.
CRIS-Team WoS Importer:2022-02-04

Combined Two-Model CFD Simulation of Trickle Bed Reactors with Head-Sump Extension: Case Study on Hydrodynamics and Biological Methanation - Markthaler, Simon; Plankenbühler, Thomas; Miederer, Jonas; Kolb, Sebastian; Herkendell, Katharina; Karl, Jürgen (Industrial & Engineering Chemistry Research, 2022)
Trickle bed reactors are one of the world’s most employed technologies for multiphase processing, and they have been scrutinized for decades. However, accurate prediction and scale-up of trickle bed reactors are still challenging owing to complex interactions of multiphase flow, interfacial mass transfer, and reaction kinetics. The present computational model provides an insight into process phenomena on the basis of Eulerian–Eulerian methodology. It captures all parts of a trickle bed reactor─packing, head, and sump─which enables simulation of co- and countercurrent flow, gas or liquid recycle, and arbitrary retention time. Applying this model, hydrodynamic simulations reveal an improved prediction of liquid holdup, liquid dispersion, and pressure drop compared to CFD models of only the trickle bed. Furthermore, the interfacial surface area is analyzed and validated on account of a literature correlation. Exemplifying the entire approach with chemical absorption and reaction, the simulation of biological methanation presents methane concentration and productivity which are of the same order of magnitude as experimental data for an operating pressure of pop = 0.1–1 MPaabs.<br

Considering the Environmental Impacts of BioenergyTechnologies to Support German Energy Transition - Kalu, Amarachi; Vrzel, Janja; Kolb, Sebastian; Karl, Jürgen; Marzahn, Philip; Pfaffenberger, Fabian; Ludwig, Ralf (Energies, 2021)

Early Detection of Agglomeration in Fluidized Beds by Means of Frequency Analysis of Pressure Fluctuations - Leimbach, Steffen; Lukas, Johannes; Kolb, Sebastian; Yang, Lei; Plankenbühler, Thomas; Sega, Marcello; Harting, Jens; Karl, Jürgen (Energy & Fuels, 2022)
For description of the fluidization state of fluidized beds, both time-domain and frequency-domain analyses of high-frequency pressure fluctuations are established approaches. Common methods for the detection of agglomeration or defluidization in fluidized beds use the variance or the standard deviation of the pressure signal or the maximum in its frequency spectrum. These methods are used, for example, in biomass combustion or gasification. However, these approaches lack the reliability for applications as an early agglomeration warning system in industrial applications. To address this issue, the present study introduces a robust methodology by means of extracting a characteristic frequency from the power spectral density of the pressure signal. A comparison of our developed approach with the commonly used frequency maximum and standard deviation for predicting the onset of agglomeration in laboratory experiments shows promising sensitivity on agglomeration formation. In order to evaluate the general applicability of this method on an industrial scale, this work investigates dependencies of possible influences, such as gas velocity, sand quantity, and temperature, on the characteristic frequency. The results indicate that the characteristic frequency can be a promising and robust method for the early detection of the onset of agglomeration in industrial plants.<br

Early Detection of Agglomeration in Fluidized Beds by Means ofFrequency Analysis of Pressure Fluctuations - Leimbach, Steffen; Lukas, Johannes; Kolb, Sebastian; Yang, Lei; Plankenbühler, Thomas; Sega, Marcello; Harting, Jens; Karl, Jürgen (Energy & Fuels, 2022)
For description of thefluidization state offluidizedbeds, both time-domain and frequency-domain analyses of high-frequency pressurefluctuations are established approaches.Common methods for the detection of agglomeration ordefluidization influidized beds use the variance or the standarddeviation of the pressure signal or the maximum in its frequencyspectrum. These methods are used, for example, in biomasscombustion or gasification. However, these approaches lack thereliability for applications as an early agglomeration warningsystem in industrial applications. To address this issue, the presentstudy introduces a robust methodology by means of extracting acharacteristic frequency from the power spectral density of thepressure signal. A comparison of our developed approach with thecommonly used frequency maximum and standard deviation for predicting the onset of agglomeration in laboratory experimentsshows promising sensitivity on agglomeration formation. In order to evaluate the general applicability of this method on an industrialscale, this work investigates dependencies of possible influences, such as gas velocity, sand quantity, and temperature, on thecharacteristic frequency. The results indicate that the characteristic frequency can be a promising and robust method for the earlydetection of the onset of agglomeration in industrial plants.

Economic Evaluation of Renewable Hydrogen Integration into Steelworks for the Production of Methanol and Methane - Bampaou, Michael; Panopoulos, Kyriakos; Seferlis, Panos; Sasiain, Amaia; Haag, Stephane; Wolf-Zoellner, Philipp; Lehner, Markus; Rog, Leokadia; Rompalski, Przemyslaw; Kolb, Sebastian; Kieberger, Nina; Dettori, Stefano; et al. (Energies, 2022)
This work investigates the cost-efficient integration of renewable hydrogen into steelworks for the production of methane and methanol as an efficient way to decarbonize the steel industry. Three case studies that utilize a mixture of steelworks off-gases (blast furnace gas, coke oven gas, and basic oxygen furnace gas), which differ on the amount of used off-gases as well as on the end product (methane and/or methanol), are analyzed and evaluated in terms of their economic performance. The most influential cost factors are identified and sensitivity analyses are conducted for different operating and economic parameters. Renewable hydrogen produced by PEM electrolysis is the most expensive component in this scheme and responsible for over 80% of the total costs. Progress in the hydrogen economy (lower electrolyzer capital costs, improved electrolyzer efficiency, and lower electricity prices) is necessary to establish this technology in the future.
CRIS-Team WoS Importer:2022-07-22

Enhancement of catalytic direct methanation for application in wastewater treatment plants - Miederer, Jonas; Markthaler, Simon; Kolb, Sebastian; Karl, Jürgen (4th Doctoral Colloquium BIOENERGY, 2021)

Environmental assessment of anaerobic digestion and biological methanation in power-to-methane systems - Elhaus, Nora; Kolb, Sebastian; Müller, Jakob; Goldbrunner, Markus; Karl, Jürgen; Herkendell, Katharina (Journal of Cleaner Production, 2023)
Biomethane can play a crucial role in achieving European climate goals and replacing natural gas. One way to increase biomethane production is through biological methanation, converting the remaining CO2 from biogas with hydrogen into methane. The required hydrogen is produced via electrolysis, making this technology also a valuable storage and balance solution for the energy grid. This study determines the ecological development potentials of biological methanation. For this purpose, different feedstock for anaerobic digestion are investigated as carbon source, effects of technological advances in electrolysis and biological methanation are determined and optimal modes of operation are evaluated. Results indicate that the biological methanation with an anaerobic digestion using manure as feedstock has the lowest greenhouse gas emissions. However, the biological methanation achieves the greatest reduction in emissions compared to traditional biomethane production (biogas upgrading with high pressurized water scrubbing) when using energy crops and reducing emissions from feedstock production. In the base scenario which represents the current state of technology, biogas from maize without additional methanation step produces 151.8 kgCO2eq/MWhCH4. In combination with biological methanation, biomethane can be produced in the future with CO2eq emissions of 121.4 kgCO2eq/MWhCH4. Other factors such as agricultural land occupation or water consumption show even more significant improvements. The main drivers of emissions are the electricity demand for the electrolysis and fugitive methane emissions. The study shows that there is great ecological potential in biological methanation, especially in the future with prognosed technological advances in electrolysis and biological methanation.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Anaerobic digestion; Biological methanation; Biomethane; Greenhouse gas emission; Life cycle assessment; Methanogenesis; Power-to-Gas; Power-to-Methane; Renewable gases

Erneuerbare Gase für das Energiesystem der Zukunft - Kolb, Sebastian; Plankenbühler, Thomas; Neubert, Michael; Karl, Jürgen (gwf: Gas+Energie, 2020)

Experimental characterization of a reversible heat pump – Organic Rankine cycle pilot plant as a thermally integrated Carnot battery - Weitzer, Maximilian; Reiß, Sabine; Steger, Daniel; Kolb, Sebastian; Karl, Jürgen (Applied Thermal Engineering, 2025)
This paper presents a first detailed experimental characterization of a reversible heat pump – Organic Rankine Cycle pilot plant, highlighting its potential as a thermally integrated Carnot battery for efficient energy storage. A total of 150 stationary operating points were investigated in both heat pump and ORC modes. The study analyzes and discusses the main trends and interactions at both the system and component levels. As expected, heat pump and ORC operations exhibit an opposing behavior. While heat pump operation yields a maximum COP of 9.5 at a 15 K temperature lift, the peak net ORC efficiency reaches 4.4 % with a 40 K temperature gradient. Neglecting additional storage losses, this leads to a power-to-power (round-trip) efficiency of up to 41.8 % for the Carnot battery. The absence of a liquid receiver in the ORC mode leads to significant subcooling and increased condensation pressures, which affect the expander's power generation due to excess refrigerant accumulation. Moreover, the experimental results reveal that the reversible screw machine is the critical factor influencing efficiency. The screw machine's maximum isentropic efficiencies are 78 % and 60 % in compressor and expander operation, respectively. The reliability of the results was verified by means of an energy balance and reference operating points, underlining high reproducibility. Additionally, potential system improvements were derived from the experimental results. Altogether, this paper successfully demonstrates the concept of reversible heat pump – ORC systems and provides experimental results for further advancements in this field.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Carnot battery; Energy storage; Experimental characterization; Heat pump; Organic Rankine Cycle

Hydrogen intensified synthesis processes to valorise process off-gases in integrated steelworks - Matino, Ismael; Dettori, Stefano; Conde, Amaia Sasian; Colla, Valentina; Petrucciani, Alice; Zaccara, Antonella; Iannino, Vincenzo; Mocci, Claudio; Hauser, Alexander; Kolb, Sebastian; Karl, Jürgen; Haag, Stéphane; et al. (Materiaux et Techniques, 2023)
Integrated steelworks off-gases are generally exploited to produce heat and electricity. However, further valorization can be achieved by using them as feedstock for the synthesis of valuable products, such as methane and methanol, with the addition of renewable hydrogen. This was the aim of the recently concluded project entitled Intelligent and integrated upgrade of carbon sources in steel industries through hydrogen intensified synthesis processes (i3upgrade). Within this project, several activities were carried out: from laboratory analyses to simulation investigations, from design, development and tests of innovative reactor concepts and of advanced process control to detailed economic analyses, business models and investigation of implementation cases. The final developed methane production reactors are, respectively, an additively manufactured structured fixed-bed reactor and a reactor setup using wash-coated honeycomb monoliths as catalyst; both reactors reached almost full COx conversion under slightly over-stoichiometric conditions. A new multi-stage concept of methanol reactor was designed, commissioned, and extensively tested at pilot-scale; it shows very effective conversion rates near to 100% for CO and slightly lower for CO2 at one-through operation for the methanol synthesis. Online tests proved that developed dispatch controller implements a smooth control strategy in real time with a temporal resolution of 1'‰ min and a forecasting horizon of 2'‰ h. Furthermore, both offline simulations and cost analyses highlighted the fundamental role of hydrogen availability and costs for the feasibility of i3upgrade solutions, and showed that the industrial implementation of the i3upgrade solutions can lead to significant environmental and economic benefits for steelworks, especially in case green electricity is available at an affordable price.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Advanced control; Carbon capture and usage; Hydrogen use; Methane synthesis; Methanol synthesis; Process-off gases valorization; Steel; Steelmaking industry sustainability

Hydrogen role in the valorization of integrated steelworks process off-gases through methane and methanol syntheses - Matino, Ismael; Dettori, Stefano; Zaccara, Antonella; Petrucciani, Alice; Iannino, Vincenzo; Colla, Valentina; Bampaou, Michael; Panopoulos, Kyriakos; Rechberger, Katharina; Kolb, Sebastian; Hauser, Alexander; Wolf-Zoellner, Philipp; et al. (Materiaux et Techniques, 2022)
The valorization of integrated steelworks process off-gases as feedstock for synthesizing methane and methanol is in line with European Green Deal challenges. However, this target can be generally achieved only through process off-gases enrichment with hydrogen and use of cutting-edge syntheses reactors coupled to advanced control systems. These aspects are addressed in the RFCS project i(3)upgrade and the central role of hydrogen was evident from the first stages of the project. First stationary scenario analyses showed that the required hydrogen amount is significant and existing renewable hydrogen production technologies are not ready to satisfy the demand in an economic perspective. The poor availability of low-cost green hydrogen as one of the main barriers for producing methane and methanol from process off-gases is further highlighted in the application of an ad-hoc developed dispatch controller for managing hydrogen intensified syntheses in integrated steelworks. The dispatch controller considers both economic and environmental impacts in the cost function and, although significant environmental benefits are obtainable by exploiting process off-gases in the syntheses, the current hydrogen costs highly affect the dispatch controller decisions. This underlines the need for big scale green hydrogen production processes and dedicated green markets for hydrogen-intensive industries, which would ensure easy access to this fundamental gas paving the way for a C-lean and more sustainable steel production.
Created from Fastlane, WoS look-up

Image-based biomass characterization: Comparison of conventional image processing and a deep learning approach - Lukas, Johannes; Kolb, Sebastian; Heinbuch, Johann; Willig, Lukas; Plankenbühler, Thomas; Müller, Dominik; Karl, Jürgen (Fuel, 2023)
Due to the increased use of inconsistent low-grade biogenic solid fuels and simultaneously stricter regulatory limitations for biomass combustion, there is a rising demand for suitable methods for an online characterization of fuels to allow for optimal plant operation. Aim of this work is to evaluate two camera-based machine vision approaches using a conventional feature extraction method based classification and a deep learning approach with a convolutional neural network (CNN) to distinguish six types of biogenic solid fuels and 20 fuel mixtures thereof. A comparison of four machine-learning algorithms applied to classify the samples based on all extracted color and texture features reaches a prediction accuracy of 93.5 %. An evaluation of the feature performance of single features shows that the selected color features (color thresholds and histogram-based features) are more relevant for distinguishing the fuels than the textural features (Haralick features and features extracted from the frequency domain). Despite the small size of the image dataset, also the CNN achieves a good prediction accuracy of 73.7 % for the given classification task. An increase of the number of images by fragmentation leads to a slightly increasing prediction accuracy for the deep learning approach while the accuracy of the conventional features learning approach decreases. Both approaches are suitable to distinguish six typical biogenic solid fuels and achieve high accuracies for the classification of 26 fuels and mixtures. While the feature learning is more accurate for the mentioned classification task, the CNN does not require prior feature extraction and would benefit from a larger dataset. These are promising results for an implementation as an online fuel monitoring in various applications, with further development in the robustness and extensions by means of a broader range of fuel mixtures being required.
CRIS-Team Scopus Importer:2023-03-31
Keywords: Biomass combustion; Deep learning; Feature extraction; Fuel monitoring; Image processing; Machine vision

Image-Based Model for Assessment of Wood Chip Quality and Mixture Ratios - Plankenbühler, Thomas; Kolb, Sebastian; Grümer, Fabian; Müller, Dominik; Karl, Jürgen (Processes, 2020)

Integration of Renewable Gases into the Gas Market: A Nonlinear Optimization Approach - Kolb, Sebastian; Dillig, Marius; Karl, Jürgen (12 th International Renewable Energy Storage Conference (IRES 2018), 2018)

Life cycle greenhouse gas emissions of renewable gas technologies: A comparative review - Kolb, Sebastian; Plankenbühler, Thomas; Homfann, Katharina; Bergerson, Joule; Karl, Jürgen (Renewable and Sustainable Energy Reviews, 2021)

Modellierung des Wärmesektors und dessen Flexibilität für Simulationen gekoppelter Energiesysteme - Luna-Jaspe Roa, Natalia; Aigner, Kevin-Martin; Kolb, Sebastian; Karl, Jürgen (EnInnov2024 - 18. Symposium Energieinnovation 2024, 2024)
Die Defossilisierung des Wärmesektors ist eine der größten Herausforderungen der europäischen Energiewende. Ohne drastische Transformation werden stark öl- und gasabhängige Länder wie Deutschland ihre Klimaziele nicht erreichen. Mögliche Entwicklungsszenarien der Literatur sehen die Elektrifizierung des Wärmesektors durch Wärmepumpen als eine der am besten geeigneten Lösungen. Doch nicht nur der Wärmesektor wird in Zukunft hohe Stromnachfragen generieren, auch andere Sektoren wie der Verkehrssektor werden stark elektrifiziert werden. In diesem Kontext spielt die Möglichkeit zur Flexibilisierung dieser Stromnachfragen eine wichtige Rolle, insbesondere mit Blick auf den Ausbau der fluktuierenden erneuerbaren Energien. Diese Arbeit analysiert das Flexibilitätspotential des Wohngebäudesektors durch die Nutzung der thermischen Gebäudemasse. Außerdem wird untersucht, wie die zur Verfügung stehende Flexibilität optimal eingesetzt werden kann. Wohngebäude können durch die Nutzung der thermischen Gebäudemasse einen Beitrag zur Flexibilisierung des Energiesystems leisten. Das Flexibilitätspotential in der Zukunft ist von der Sanierungstiefe abhängig. Die Effekte von Flexibilitätsmaßnahmen auf die Kosten und die Netzentlastung sind zusätzlich von den gewählten Optimierungsbedingungen abhängig.<br
Keywords: Simulationsmodell; Wärmesektor; thermische Gebäudemasse; Flexibilisierung; Optimierung

Multi-agent systems to improve efficiency in steelworks - Iannino, Vincenzo; Colla, Valentina; Mocci, Claudio; Matino, Ismael; Dettori, Stefano; Kolb, Sebastian; Plankenbühler, Thomas; Karl, Jürgen (Materiaux et Techniques, 2021)
A multi-agent system consists of several computational entities capable of autonomous actions, called agents, which communicate with each other, and have the ability to coordinate their actions and to cooperate. Multi-agent systems received a great interest and attention over time, as they can be seen as a key enabling technology for complex applications, where distributed and processing of data, autonomy, and high degree of interactions in dynamic environments are required at the same time. Therefore, in view of current and future developments of the digitalization of industrial production cycles promoted by Industry 4.0, multi-agent systems are foreseen to play an increasing role for industrial production management and optimization. Because of barriers represented by large presence of legacy systems, in the steel sector agent-based technology is not widely applied yet, and multi-agent systems applications are very few. On the other hand, steel manufacturing industries are complex and dynamic systems whose production processes held a strategic role in the global economy. During last decades, the steel sector has undergone relevant transformations, especially through the massive digitalization and the innovation introduced by Industry 4.0. A further evolution is foreseen in the incoming years to improve the sustainability of the production cycle by improving energy and resource efficiency. Therefore, steel industries must face several challenges on the path toward the factory of the future. In such context multi-agent systems, through their intrinsic properties, such as autonomy, social abilities, reactivity, proactivity, and mobility, can overcome existing drawbacks and barriers, by increasing flexibility, improving resources efficiency, handling production operations, reacting to unpredicted events, optimizing production processes, and supporting legacy systems. In this paper, some applications of multi-agent systems in steel sector are presented to show the advantages and opportunities of agent-based technology.
Created from Fastlane, Scopus look-up
Keywords: Dynamic resources allocation; Industry 4.0; Multi-Agent Systems; Off-gas management; Steel industry; Sustainability

Renewable Gases for the German Gas Market – A model-based Scenario Analysis - Kolb, Sebastian (4th Doctoral Colloquium BIOENERGY, 2021)

Renewable hydrogen imports for the German energy transition-A comparative life cycle assessment - Kolb, Sebastian; Müller, Jakob; Luna-Jaspe, Natalia; Karl, Jürgen (Journal of Cleaner Production, 2022)
Hydrogen imports are considered as a promising pillar for the defossilisation of the German energy system. One of the main concerns when discussing hydrogen solutions is its environmental performance, especially with regard to its greenhouse gas emissions. While a large number of life cycle assessments (LCA) helps to thoroughly understand the impacts of domestic hydrogen production, the assessment of international supply chains remains scarce. On that account, this study performs a comparative LCA of liquefied hydrogen imports from Chile, Canada and Morocco to Germany in a cradle-to-gate approach. A scenario and sensitivity analysis allows to analyse the main drivers on the ecological meaningfulness and to derive recommendations for the establishment of renewable hydrogen supply chains. The results show that the import of renewable hydrogen can outperform domestic production in some cases. In the defined base case, the global warming potential of hydrogen delivered to the German gas grid ranges from 1.505 to 2.457 kgCO2eq/kgH2 or 45.2 to 73.7 gCO2eq/kWhH2,LHV for windbased imports. Domestically produced hydrogen from wind shows emissions of 1.989 kgCO2eq/kgH2 or 59.7 gCO2eq/kWhH2,LHV. Results for hydrogen produced by solar PV range from 3.787 to 4.008 kgCO2eq/kgH2 or 113.6 to 120.3 gCO2eq/kWhH2,LHV for imports (5.195 kgCO2eq/kgH2 or 155.9 gCO2eq/kWhH2,LHV for domestic production). However, while for domestic hydrogen electrolysis is by far the predominant process step, the entire process chain needs to be taken into consideration for importing cases (e.g. the shipping distance and fuel, the electricity source for hydrogen liquefaction).
Keywords: Hydrogen; Liquid hydrogen; Renewable gases; Energy transport; Life cycle assessment; Greenhouse gas emissions

Renewable hydrogen imports for the German energy transition-A comparative life cycle assessment - Kolb, Sebastian; Müller, Jakob; Luna-Jaspe, Natalia; Karl, Jürgen (Journal of Cleaner Production, 2022)
Hydrogen imports are considered as a promising pillar for the defossilisation of the German energy system. One of the main concerns when discussing hydrogen solutions is its environmental performance, especially with regard to its greenhouse gas emissions. While a large number of life cycle assessments (LCA) helps to thoroughly understand the impacts of domestic hydrogen production, the assessment of international supply chains remains scarce. On that account, this study performs a comparative LCA of liquefied hydrogen imports from Chile, Canada and Morocco to Germany in a cradle-to-gate approach. A scenario and sensitivity analysis allows to analyse the main drivers on the ecological meaningfulness and to derive recommendations for the establishment of renewable hydrogen supply chains. The results show that the import of renewable hydrogen can outperform domestic production in some cases. In the defined base case, the global warming potential of hydrogen delivered to the German gas grid ranges from 1.505 to 2.457 kgCO2eq/kgH2 or 45.2 to 73.7 gCO2eq/kWhH2,LHV for windbased imports. Domestically produced hydrogen from wind shows emissions of 1.989 kgCO2eq/kgH2 or 59.7 gCO2eq/kWhH2,LHV. Results for hydrogen produced by solar PV range from 3.787 to 4.008 kgCO2eq/kgH2 or 113.6 to 120.3 gCO2eq/kWhH2,LHV for imports (5.195 kgCO2eq/kgH2 or 155.9 gCO2eq/kWhH2,LHV for domestic production). However, while for domestic hydrogen electrolysis is by far the predominant process step, the entire process chain needs to be taken into consideration for importing cases (e.g. the shipping distance and fuel, the electricity source for hydrogen liquefaction).
Keywords: Hydrogen; Liquid hydrogen; Renewable gases; Energy transport; Life cycle assessment; Greenhouse gas emissions

Renewable hydrogen imports for the German energy transition – A comparative life cycle assessment - Kolb, Sebastian; Müller, Jakob; Luna-Jaspe Roa, Natalia; Karl, Jürgen (Journal of Cleaner Production, 2022)
Hydrogen imports are considered as a promising pillar for the defossilisation of the German energy system. One of the main concerns when discussing hydrogen solutions is its environmental performance, especially with regard to its greenhouse gas emissions. While a large number of life cycle assessments (LCA) helps to thoroughly understand the impacts of domestic hydrogen production, the assessment of international supply chains remains scarce. On that account, this study performs a comparative LCA of liquefied hydrogen imports from Chile, Canada and Morocco to Germany in a cradle-to-gate approach. A scenario and sensitivity analysis allows to analyse the main drivers on the ecological meaningfulness and to derive recommendations for the establishment of renewable hydrogen supply chains. The results show that the import of renewable hydrogen can outperform domestic production in some cases. In the defined base case, the global warming potential of hydrogen delivered to the German gas grid ranges from 1.505 to 2.457 kgCO2eq/kgH2 or 45.2 to 73.7 gCO2eq/kWhH2,LHV for wind-based imports. Domestically produced hydrogen from wind shows emissions of 1.989 kgCO2eq/kgH2 or 59.7 gCO2eq/kWhH2,LHV. Results for hydrogen produced by solar PV range from 3.787 to 4.008 kgCO2eq/kgH2 or 113.6 to 120.3 gCO2eq/kWhH2,LHV for imports (5.195 kgCO2eq/kgH2 or 155.9 gCO2eq/kWhH2,LHV for domestic production). However, while for domestic hydrogen electrolysis is by far the predominant process step, the entire process chain needs to be taken into consideration for importing cases (e.g. the shipping distance and fuel, the electricity source for hydrogen liquefaction).<br

REVERSIBLE HEAT PUMP-ORC PILOT PLANT – EXPERIMENTAL RESULTS AND FLUID CHARGE OPTIMIZATION - Weitzer, Maximilian; Kolb, Sebastian; Müller, Dominik; Karl, Jürgen (7th International Seminar on ORC Power Systems, 2023)

Scenario-based analysis for the integration of renewable gases into the german gas market - Kolb, Sebastian; Plankenbühler, Thomas; Pfaffenberger, Fabian; Vrzel, Janja; Kalu, Amarachi; Holtz-Bacha, Christina; Ludwig, Ralf; Karl, Jürgen; Dillig, Marius (3. Prasenztreffen Forschungsnetzwerk Energiesystemanalyse, 2019)

Scenario-based analysis for the integration of renewable gases into the german gas market - Kolb, Sebastian; Plankenbühler, Thomas; Pfaffenberger, Fabian; Vrzel, J.; Kalu, A.; Holtz-Bacha, Christina; Ludwig, R.; Karl, Jürgen; Dillig, Marius (European Biomass Conference and Exhibition Proceedings, 2019)
The German energy system is highly dependent on the use of fossil gas. It is considered to be a “green” fossil energy carrier whose importance is even expected to rise in times of high shares of volatile renewable electricity in the grid. However, to reduce the dependence on imported natural gas and further increase the share of renewables in the energy mix, numerous technologies aim to substitute natural gas with green, renewable gas. Those technologies are promising, yet mostly not economically feasible under the current market situation. To face this issue, the Chair of Energy Process Engineering at Friedrich-Alexander University Erlangen-Nuremberg (FAU) developed a simulation-based optimisation model to analyse and compare different (funding) strategies to integrate renewable gases into the German gas market until 2050. Main focus of the model lies on a detailed description of the different technological options as well as a realistic mapping of the gas market’s behaviour. In doing so, the possible effects of different funding scenarios and quantities on the future gas mix, CO2 emissions and gas prices could be evaluated.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Biomass; Market forecasts; Modelling; Policies; Strategies

Scenarios for the Integration of Renewable Gases into the German Gas Market: A simulation based Optimisation Approach - Kolb, Sebastian; Plankenbühler, Thomas; Dillig, Marius; Karl, Jürgen (Jahrestreffen der ProcessNet Fachgruppe EVT, 2019)

Scenarios for the integration of renewable gases into the German natural gas market – A simulation-based optimisation approach - Kolb, Sebastian; Plankenbühler, Thomas; Frank, Jonas; Dettelbacher, Johannes; Ludwig, Ralf; Karl, Jürgen; Dillig, Marius (Renewable & Sustainable Energy Reviews, 2021)
Natural gas plays an essential role in Germany's energy system, both in the heating and electricity sectors. In order to achieve climate goals, numerous technologies aim at substituting fossil with renewable gas. Those technologies start reaching technical maturity, yet they are mostly not economically competitive under the current market conditions. To find transition paths to resolve this issue this paper introduces the simulation-based optimisation model MIREG (Model for the Integration of Renewable Gases). Combining a system-dynamic simulation of the various renewable gas options with an optimisation model of the gas market, the model puts strong focus on the reproduction of gas market's mechanisms and the implications of a rising penetration of renewable gases. The model is then applied to analyse the effects of different developments of market conditions and funding strategies on the possible share of renewable gases in the German gas mix until 2050. Results show that if renewable gases are supposed to account for a significant share of gas consumed in Germany they either need to be funded substantially or market conditions have to change. For a share of 23% renewable gas in the gas mix CO2 prices for example would have to reach a level of 150 €/tCO2 by 2050 (300 €/tCO2 for 54%). The scenarios also indicate that in order to meet significant amounts of the German gas consumption with renewable gases, international solutions need to be aimed at e.g. by importing renewable gas from locations with high potential of renewable energy or by importing biomass.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Biomethane; Energy system modeling; Power-to-Hydrogen; Power-to-Methane; Scenario analysis; Synthetic natural gas

Short-Term Natural Gas and Carbon Price Forecasting Using Artificial Neural Networks - Böhm, Laura; Kolb, Sebastian; Plankenbühler, Thomas; Miederer, Jonas; Markthaler, Simon; Karl, Jürgen (Energies, 2023)
Methods of computational intelligence show a high potential for short-term price forecasting of the energy market as they offer the possibility to cope with the complexity, multi-parameter dependency, and non-linearity of pricing mechanisms. While there is a large number of publications applying neural networks to the prediction of electricity prices, the analysis of natural gas and carbon prices remains scarce. Identifying a best practice from the literature, this study presents an iterative approach to optimize both the input values and network configuration of neural networks. We apply the approach to the natural gas and carbon market, sequentially testing autoregressive and exogenous explanatory variables as well as different neural network architectures. We subsequently discuss the influence of architectural properties, input parameters, data preparation, and the models’ resilience to singular events. Results show that the selection of appropriate lags of gas and carbon prices to account for autoregressive properties of the respective time series leads to a high degree of forecasting accuracy. Additionally, including ambient temperature data can slightly reduce errors of natural gas price forecasting whereas carbon price predictions benefit from electricity prices as a further explanatory input. The best configurations presented in this contribution achieve a root mean square error (RMSE) of 0.64 EUR/MWh (natural gas prices) corresponding to a normalized RMSE of 0.037 and 0.33 EUR/tCO2 (carbon prices) corresponding to a normalized RMSE of 0.023.
CRIS-Team Scopus Importer:2023-10-06
Keywords: carbon price; multi-layer perceptron; natural gas price; neural network; price prediction

SustainableGas - Model for the Integration of Renewable Gases (MIREG) - Kolb, Sebastian; Plankenbühler, Thomas; Karl, Jürgen; Dillig, Marius (2. Präsenztreffen Forschungsnetzwerk Energiesystemanalyse, 2018)

Techno-economic evaluation of anaerobic digestion and biological methanation in Power-to-Methane-Systems - Elhaus, Nora; Volkmann, Maximilian; Kolb, Sebastian; Schindhelm, Lucas; Herkendell, Katharina; Karl, Jürgen (Energy Conversion and Management, 2024)
Keywords: Power-to-Methane; Renewable gases; Methanogenesis; Power-to-Gas; Techno-economic assessment; Biological Methanation

The impact of renewables on electricity prices in Germany - An update for the years 2014–2018 - Kolb, Sebastian; Dillig, Marius; Plankenbühler, Thomas; Karl, Jürgen (Renewable and Sustainable Energy Reviews, 2020)
Increasing electricity prices for private consumers manifested the idea of price boosting renewable energy sources in Germany's public opinion. Literature however widely concurs that wind and photovoltaics have a reducing effect on spot market electricity prices. The underlying merit order effect led to historically low exchange prices in the past years. To quantify this effect, this study analyses historic demand and supply curves from the German day-ahead market to reconstruct electricity prices without the feed-in of wind and photovoltaics from 2014 to 2018. Results show that renewable energy sources considerably reduced electricity prices by between 2.89 ct/kWh in 2014 to 8.89 ct/kWh in 2017. This allowed German end-consumers to save a total of 40 billion € from 2014 to 2018. Additionally, wind and PV contributed significantly to security of supply. Demand could not have been met by domestic conventional and nuclear generation capacities in up to 424 hours in 2018. The study highlights the necessity to further speed-up the expansion of wind and photovoltaics.<br
Keywords: Electricity price modelling; Energy economics; Merit order effect; Renewable electricity; Renewable energy systems; Security of supply

Valorizing Steelworks Gases by Coupling Novel Methane and Methanol Synthesis Reactors with an Economic Hybrid Model Predictive Controller - Hauser, Alexander; Wolf-Zoellner, Philipp; Haag, Stephane; Dettori, Stefano; Tang, Xiaoliang; Mighani, Moein; Matino, Ismael; Mocci, Claudio; Colla, Valentina; Kolb, Sebastian; Bampaou, Michael; Panopoulos, Kyriakos; et al. (Metals, 2022)
To achieve the greenhouse gas reduction targets formulated in the European Green Deal, energy- and resource-intensive industries such as the steel industry will have to adapt or convert their production. In the long term, new technologies are promising. However, carbon capture storage and utilization solutions could be considered as short-term retrofitting solutions for existing steelworks. In this context, this paper presents a first experimental demonstration of an approach to the utilization of process off-gases generated in a steelworks by producing methane and methanol in hydrogen-intensified syntheses. Specifically, the integration of two methane synthesis reactors and one methanol synthesis reactor into a steel plant is experimentally simulated. An innovative monitoring and control tool, namely, a dispatch controller, simulates the process off-gas production using a digital twin of the steel plant and optimizes its distribution to existing and new consumers. The operating states/modes of the three reactors resulting from the optimization problem to be solved by the dispatch controller are distributed in real time via an online OPC UA connection to the corresponding experimental plants or their operators and applied there in a decentralized manner. The live coupling test showed that operating values for the different systems can be distributed in parallel from the dispatch controller to the test rigs via the established communication structure without loss. The calculation of a suitable control strategy is performed with a time resolution of one minute, taking into account the three reactors and the relevant steelworks components. Two of each of the methane/methanol synthesis reactors were operated error-free at one time for 10 and 7 h, respectively, with datasets provided by the dispatch controller. All three reactor systems were able to react quickly and stably to dynamic changes in the load or feed gas composition. Consistently high conversions and yields were achieved with low by-product formation.
CRIS-Team WoS Importer:2022-07-08

Wasserstoff in der Metropolregion Nürnberg – Analyse der Kompetenzen, Chancen und Herausforderungen - Pircher, Thomas; Bazan, Peter; Elhaus, Nora; Fellerer, Jonathan; German, Reinhard; Karl, Jürgen; Kolb, Sebastian; Kunz, Thomas; Opferkuch, Frank; Pilz-Lansley, Alexander; Reichenwallner, Simon; Ronge, Karlheinz; et al. (2023)
The study shows that the metropolitan region has economic potential in the product-related value chain. Depending on the scenario, this market sector can become a decisive factor and will create jobs in several fields in the European Metropolitan Region Nuremberg (EMN). However, the simulations show that the generation potential from energy surpluses is not sufficient for significant export. However, the own production of hydrogen in the metropolitan region could cover the own demand, mainly heavy duty vehicles and process heat, and thus could also be an incentive for the own infrastructure development. However, the simulation clearly shows that a pushed expansion of renewable energies is indispensable and that the storage capacities and concepts planned so far will not be sufficient to buffer the surplus energy peaks and make them available. There is a need for research and action here, both specifically for the EMN and for other regions. From our point of view, it will be crucial for the EMN that the existing industry in the EMN acquires the competences to develop and produce components, partial and complete systems for hydrogen technology. For this purpose, it is important to provide easy access to this knowledge in the form of a central knowledge center and to ensure close networking of the various players in the product-related value chai
Keywords: hydrogen; european metropolitan area; mobility; sector coupling